Global Operations Strategy Fundamentals and Practice - Gong, Yeming; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
While many business schools are teaching (3z(BGlobal Operations Strategy(3y (Bwith self-made teaching materials, there are no such textbooks. Combining practical approaches with detailed theoretical underpinnings, this book provides theories, tools, frameworks, and techniques for global operations strategy, and brings real world perspectives to students and managers. Each chapter includes definition of key terms, introduction of fundamental theories, several short case examples, one long new case to explain the associated theories, and recommended further reading.s
Introduction in Global Operations Strategy: Basic Concepts of Global Operations Strategy -- Globalization of Operations -- Rationale Behind Operational Globalization -- Fundamentals of Global Operations Strategy: Competency-based Fundamentals -- Resource-based Fundamentals -- Process-based Fundamentals -- Practice of Global Operations Strategy: Cross-border Global Operational Practice -- Cross-function Global Operational Practice -- Cross-value Global Operational Practice.
Keywords: Economics; Operations research; Business planning; Economics/Management Science; Business Strategy/Leadership.; Organization/Planning.; Operation Research/Decision Theory